Of Two-Spirit and Indigenous Queerness: Indigenous Queerness Today - Côté-Saucier, Nicolas (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
This article examines Indigenous queerness by moving beyond the literal definition of “two-spirit” to explore the diversity and commonalities of Indigenous queer identities. Through detailed analysis of three distinct examples—the Diné/Navajo Nádleehi, the Shoshone Tainna wa'ippe, and the Inuit Sipiniq—this article demonstrates the vast differences in Indigenous gender systems while identifying four unifying characteristics: spirituality, fluid notions of gender/sexuality, connections to tradition, and a state of “in-betweenness.” This article concludes by examining contemporary indigiqueer realities, highlighting ongoing challenges such as historical disconnection, community homophobia, racism in queer spaces, and lack of intersectional approaches, while acknowledging positive social changes and increasing representation in mainstream media.